Las matemáticas del cambio en la secundaria: Un análisis de textos - Pérez Ruiz, René (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
In the First chapter the antecedents of the investigation conform; some research is cited on the difficulties presented by the subject of variation; the justification and approach of the research problem; this is a general objective and specific objectives and research questions. In the second chapter we make a brief review of the research on the different contents related to the variation; we begin with those that have a historical focus, and then continue with the studies that focus their attention on the learning problems that, for the students, implies this notion. In addition to the vision about the concept of function in the curricular proposal of the Principles and Standards for School Mathematics (NCTM, 2000), which is one of the most influential curricular proposals of recent times, raised by the National Council of Teachers of Mathematics. In this curricular proposal it is conceived to achieve the fines of the education through six principles (equality, curricular, teaching, learning, evaluation and technological) and ten standards; Five of them refer to the content lines (numbers and operations, algebra, geometry, measurement, data analysis and probability) and the other five standards refer to thought processes: problem solving, reasoning and demonstration, communication, And representation. The third chapter refers to the analysis of the curricular documents elaborated by the SEP from the Educational Reforms of 1993 and 2006 and to the Book for the Master. The fourth chapter refers to the analysis of secondary school textbooks, from which five textbooks were analyzed, from the first to the third year, three books from the 2006 plan (Mancera, Escañero and Briseño) and two books from the 2006 plan. Plan 1993 (Waldegg and Zúñiga).

En el Primer capítulo lo conforman los antecedentes de la investigación; se cita algunas investigaciones hechas sobre las dificultades que presenta el tema de variación; la justificación y Planteamiento del problema de investigación; la cual se conforma de objetivo general y objetivos específicos y las preguntas de investigación. En el Segundo capítulo hacemos una revisión breve de investigación sobre diferentes aspectos relacionados con la variación; iniciamos con aquellas que tienen un enfoque histórico, para luego continuar con estudios que centran su atención sobre los problemas de aprendizaje que, para los alumnos, implica esta noción. Además la visión sobre el concepto de función en la propuesta curricular de los Principios y Estándares para las Matemáticas Escolares (NCTM, 2000), que es una de las propuestas curriculares más influyente en los últimos tiempos, planteada por el Consejo Nacional de Profesores de Matemáticas. En esta propuesta curricular se concibe alcanzar los fines de la educación a través de seis principios (igualdad, curricular, enseñanza, aprendizaje, evaluación y tecnológico) y diez estándares; cinco de los cuales se refieren a líneas de contenido (números y operaciones, álgebra, geometría, medición, análisis de datos y probabilidad) y los otros cinco estándares se refieren a procesos de pensamiento: resolución de problemas, razonamiento y demostración, comunicación, conexiones y representación. El Tercer capítulo se refiere al análisis de los documentos curriculares elaborados por la SEP a partir de las Reformas Educativas de 1993 y 2006 y el Libro para el Maestro. El Cuarto capítulo se refiere al análisis de libros de texto de nivel secundaria, de los cuales se realizó el análisis de cinco libros de texto, desde primero hasta tercer año, tres libros del plan 2006 (Mancera, Escañero y Briseño) y dos del plan 1993 (Waldegg y Zúñiga).
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Educación Matemática
Keywords: info:eu-repo/classification/cti/1; FISMAT-M-2012-0001; Análisis; Secundaria; Educación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3255